Behavioral Factors of Fruits Merchants of Formalin Content on Imported Apples in Fruit Market of Kendari City - Silondae, Isra Khairunissa Irwan (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Apples as one of the commercial fruits consumed mostly by society are economically high value plants as world commodity moreover they are favorable and rich in vitamin. Formalin is a harmful preservative and is not allowed to be used on food. Although, formalin utilization is inhibited by the government, yet it is still used numerously by many sellers. This study aimed to understand behavioral factors of fruit seller toward formalin contents on imported apples of Fruit market in Kendari 2015. This study was descriptive with laboratory test to describe behavioral factors of fruit seller toward formalin contents through exhausted sampling technique. The object of study was 12 respondents with 48 samples of apples spread out of Fruit Market in Kendari City. The results of the study indicated that all knowledge of seller about formalin literally was good which was 100%, all attitude of seller about formalin  was good which was 100%, and all practice of seller about formaline  was good which was 100% of fruit sellers did not add formalin to the fruits. On the other hand, based on laboratory test it showed that 8 apples (16.7%) positively contained formalin. It is suggested to improve control and inspection periodically on apples to diminish prohibited preservative like formalin on fruits.